2006
DOI: 10.1007/s10734-006-9020-x
|View full text |Cite
|
Sign up to set email alerts
|

“I Heard it through the Grapevine”: Doctoral Student Socialization in Chemistry and History

Abstract: Twenty doctoral students in the disciplines of chemistry and history were interviewed to better understand the socialization processes that influence their success and how these processes differ by year in the degree program and disciplinary culture. Five major themes emerged describing these socialization processes and how they facilitate or impede degree success, including Ambiguity, describing the programmatic guidelines and expectations that surrounded much of the students' experience; Balance, pointing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
336
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(358 citation statements)
references
References 17 publications
15
336
0
7
Order By: Relevance
“…The role of peers in doctoral students' experience has received some attention (Gardner 2007;Hadjioannou et al 2007;Walsh 2010). Gardner (2007) revealed that students both in history and chemistry highlighted the importance of support from their peers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of peers in doctoral students' experience has received some attention (Gardner 2007;Hadjioannou et al 2007;Walsh 2010). Gardner (2007) revealed that students both in history and chemistry highlighted the importance of support from their peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gardner (2007) revealed that students both in history and chemistry highlighted the importance of support from their peers. The newer students look to more advanced ones as mentors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Doctoral students have, for instance, been found to emphasize social support, interaction with researchers, and adequate funding as key resources in their studies (Gardner, 2007). Also doctoral students' and supervisors' perceptions about the frequency of supervision have been shown to differ (Pyhältö, Vekkaila & Keskinen, in press).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that instead of following core phases, doctoral students conceptualise their doctoral research process on the immediate scholarly environment in which they are situated (Gardner, 2007;Pyhältö, Stubb, & Lonka, 2009;Stubb et al, 2011). In this way, students will look for and adopt views and practices they perceive to be useful (Sweitzer, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%